Genetic Structure of the Goniopora lobata and G. djiboutiensis Species Complex Is Better Explained by Oceanography Than by Morphological Characteristics - Yasuda, Nina; Kitano, Yuko F.; Taninaka, Hiroki; Nagai, Satoshi; Mezaki, Takuma; Yamashita, Hiroshi (Frontiers in Marine Science, 2021)
Species delimitation of closely related corals is often challenging due to high intraspecies morphological variation and phenotypic plasticity with a lack of characteristic features and scarcity of relevant molecular markers. Goniopora spp. are one such coralline group, and the species status of Goniopora lobata and Goniopora djiboutiensis, an Indian and Pacific Ocean hermatypic coral species complex, has been questioned on the basis of previous molecular and morphological analyses. To further examine the species boundaries between G. lobata and G. djiboutiensis in Japan, specimens collected from areas spanning from Ryukyu Island to temperate Japanese regions were morphologically identified based on traditional morphological descriptions. Then, the genetic structure of the G. lobata and G. djiboutiensis species complex was examined using six newly developed microsatellite markers. The majority of the collected specimens had intermediate morphologies, and a STRUCTURE analysis using the LOCPRIOR model based on typical G. lobata and G. djiboutiensis morphology indicated that there were no genetic differences between these morphologies. On the other hand, STRUCTURE analysis based on oceanographic regions revealed that there was a genetic break between the temperate and subtropical regions. This weak genetic break corresponded with the Kuroshio-associated barrier, which prevents larval transport between subtropical and temperate regions. This study confirms that the current morphological identification criteria for G. lobata and G. djiboutiensis do not match the existing genetic boundaries and thus the two should be regarded as a species complex. This study also highlighted the robustness of using a multi-locus population genetic approach, including a geographic context, to confirm the species boundaries of closely related species.